Caspase-independent programmed cell death triggers Ca2PO4 deposition in an in vitro model of nephrocalcinosis. Issue 1 (17th January 2018) - Priante, Giovanna; Quaggio, Federica; Gianesello, Lisa; Ceol, Monica; Cristofaro, Rosalba; Terrin, Liliana; Furlan, Claudio; Del Prete, Dorella; Anglani, Franca
Abstract : Nephrocalcinosis involves the deposition of microscopic crystals in the tubular lumen or interstitium. While the clinical, biochemical, and genetic aspects of the diseases causing nephrocalcinosis have been elucidated, little is known about the cellular events in this calcification process. We previously reported a phenomenon involving the spontaneous formation of Ca2 PO4 nodules in primary papillary renal cells from a patient with medullary nephrocalcinosis harboring a rare glial cell-derived neurotrophic factor ( GDNF ) gene variant. We also demonstrated that cultivating GDNF -silenced human kidney-2 (HK-2) cells in osteogenic conditions for 15 days triggered Ca2 PO4 deposits. Given the reportedly close relationship between cell death and pathological calcification, aim of the present study was to investigate whether apoptosis is involved in the calcification of GDNF -silenced HK-2 cells under osteogenic conditions. Silenced and control cells were cultured in standard and osteogenic medium for 1, 5, and 15 days, and any Ca2 PO4 deposition was identified by means of von Kossa staining and environmental SEM (ESEM) analyses. Based on the results of annexin V and propidium iodide (PI) analysis, and terminal deoxynucleotidyl transferase dUTP-biotin nick end labeling (TUNEL) assay, the silenced cells in the osteogenic medium showed a significant increase in the percentage of cells in the late phase of apoptosis and an increased Ca2 PO4 deposition at 15 days. The results of quantitative real-time PCR (qRT-PCR) of BAX and BCL2, and in-cell Western analysis of caspases indicated that the cell death process was independent of caspase-3, -6, -7, and -9 activation, however. Using this model, we provide evidence of caspase-independent cell death triggering the calcification process in GDNF -silenced HK-2 cells.